An Affair to Remember: Winoque, 1965 - McFeat, Tom (Culture, 1983)
Following the exclusion of their children from the nearby Anglo high school in June 1965, a series of events occurred at the reserve community of Winoque which culminated in an apparently unrelated dispute over the proposed use of band funds to secure independence from the town.The community had been divided between two factions, self-defined as crowds. The leader of the crowd I identified as Restricters was the chief; the leader of the other crowd I identified as Extenders would be that chiefs opposition in the November elections.Crowds then, were in part ideologically committed to action at the Indian/non Indian boundary. Restricters idealized this as a barrier or void whereas Extenders idealized it as a path or boundary zone. Put to the test in the issue of whether the community should send its children back to the high school, if invited, the crowds were forced to modify positions in the face of public opinion.